2015
DOI: 10.1007/s10237-015-0741-6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of boundary conditions on yield properties of human femoral trabecular bone

Abstract: Trabecular bone plays an important mechanical role in bone fractures and implant stability. Homogenized nonlinear finite element (FE) analysis of whole bones can deliver improved fracture risk and implant loosening assessment. Such simulations require the knowledge of mechanical properties such as an appropriate yield behavior and criterion for trabecular bone. Identification of a complete yield surface is extremely difficult experimentally but can be achieved in silico by using micro-FE analysis on cubical tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(55 citation statements)
references
References 36 publications
1
51
0
Order By: Relevance
“…We also observed predominance of tensile solid phase strains in pure macroscopic shear, which is consistent with Sanyal et al (2012). Multilinear regressions suggest that uniaxial yield strains are not correlated with BV/TV and fabric (Matsuura et al, 2008; Morgan and Keaveny, 2001;Panyasantisuk et al, 2015). Only a mild dependence was found for the uniaxial compressive yield strains (R 2 ¼0.44, p-0), with a positive slope for density and a negative slope for fabric, which suggests that long trabeculae, i.e.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…We also observed predominance of tensile solid phase strains in pure macroscopic shear, which is consistent with Sanyal et al (2012). Multilinear regressions suggest that uniaxial yield strains are not correlated with BV/TV and fabric (Matsuura et al, 2008; Morgan and Keaveny, 2001;Panyasantisuk et al, 2015). Only a mild dependence was found for the uniaxial compressive yield strains (R 2 ¼0.44, p-0), with a positive slope for density and a negative slope for fabric, which suggests that long trabeculae, i.e.…”
Section: Discussionsupporting
confidence: 85%
“…Our study considered yield points arising from 160 different load cases. Some recent studies have been limited to 17 load cases (Panyasantisuk et al, 2015;Wolfram et al, 2012). In order to compare our results we considered 17 strain cases similar to those in the cited studies.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Thirteen different load cases, uniaxial tension in three directions, uniaxial compression in three directions, shear in three planes, triaxial tension and compression, and two multiaxial load cases are investigated to determine the strength surface in apparent stress space. The two multiaxial load cases are characterised by tensile loading in the 1 and 2 directions together with compression in 3 direction (load case 13) and compression in 1 and 2 directions as well as tension in 3 direction (load cases 16 in Panyasantisuk et al). The 13 load cases are applied to the same three trabecular bone samples using force‐controlled PMUBCs …”
Section: Methodsmentioning
confidence: 99%
“…Each cubic specimen was investigated under 17 different uniaxial and multiaxial load cases. A generalised anisotropic quadric yield criterion by Schwiedrzik et al was fitted to the results of μFE analyses in multiple studies . Panyasantisuk et al showed the effect of the applied boundary conditions in μFE simulations on the size of the yield surfaces in stress space.…”
Section: Introductionmentioning
confidence: 99%